Evaluating the modified NUTRIC score as a prognostic tool in the intensive care unit for COVID-19 patients - Tutal Gürsoy, Görkem; Kayalı Şendur, Nuriye; Hayran, Yıldız; Yamanel , Levent; Bektaş, Hesna (Acta Medica, 2023)
Objective: The modified NUTRIC Score (mNUTRIC) score is a screening test designed for evaluating patients in intensive care units. In this study, our aim is to assess the ability of this test to predict mortality, length of hospital stay, and the need for mechanical ventilation in COVID-19 patients in the intensive care units. Materials and Methods: In our retrospective study, we evaluated 67 patients admitted to our COVID-19 intensive care unit between October and November 2020. We analyzed their entry scores and conducted general follow-up assessments. Results: In our study, we found that mortality assessment revealed a significant association between older age (p<0.001), the need for mechanical ventilation (p=0.001), and the presence of dysphagia (p<0.001) in patients who did not survive. Statistically significant findings indicate that patients classified as having high mNUTRIC scores had higher rates of 28-day mortality, the need for mechanical ventilation, and the presence of dysphagia compared to those classified as having low nutritional scores. When patients with neurodegenerative diseases were evaluated as a separate group, no significant association was found between high nutritional scores and mortality, the need for mechanical ventilation, or length of hospital stay. Conclusion: The evaluation of nutritional risk in patients being monitored in intensive care is an important step in patient management. The modified NUTRIC score is a preferable assessment test due to its ease of use.